The Role of Emotion in the Teacher Identity Construction of English Novice Teachers - Ardhitya Nugrahatama Tjuana; Sidónio António Pires (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Emotion plays an essential role for teachers because it can determine learning success. Not only that, emotion is also a crucial in constructing teacher identity, especially for novice teachers. The objective of this study is to investigate how novice teachers manage their emotions to construct their identities. This study was qualitative research at a university in Central Java. The participants were 10 novice teachers. An interview and the distribution of a questionnaire were used to gather the data. The questionnaire was distributed on Google Form, and the interview was conducted face-to-face. A Microsoft Word document would be used for transcribing the interview results, and after that, the researcher would classify and put them into the tables. The results showed that there are some strategies and techniques used by novice teachers to manage their emotions, such as seeking support, building boundaries with students, learning emotion regulation techniques, self-evaluation, engaging in the professional community, engaging in hobbies in the teaching process, and seeking feedback